Dynamic scheduling of design activities with resource constraints - Belhe, U.; Kusiak, A. (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 1997)
A design process can be represented as a network of design activities. A number of design projects may be undertaken simultaneously. This paper deals with the problem of scheduling design activities of multiple design projects competing for the limited available resources. The problem of determining a schedule subject to precedence and resource constraints is difficult to solve. It becomes even more complex when unforeseen changes are considered, for example, in the level of resources. Therefore, the scheduling problem is decomposed into a series of multidimensional (multiresource) knapsack problems. Due to high computational complexity of the multidimensional knapsack problem, two solution procedures are proposed.